SHOWING DIGNITY IN DRAMA PANTOMIME (2011) BY DEREK WALCOTT - Rio Agustianto; An Fauzia Rozani Syafei (English Language and Literature, 2019)
The purpose of this analysis is to expose the issue of showing dignity which is done by Black person and to know the contribution of the plot, spectacle, and character in revealing the showing dignity. This analysis is related to the concept of life instincts by Freud, the concept of self-awareness by Crisp-Turner and the concept of power by Michel Foucault that is supported by the text and context based interpretation. The result of this analysis shows the protagonist succeeds to show his dignity that can be seen from his knowledge and good manners.